Karakteristik Dan Kepatuhan Pada Penderita Diabetes Mellitus Tipe 2 Di Kota Lhokseumawe - Linda Adriani; Ermi Girsang; Tiarnida Nababan (Jurnal Ragam Pengabdian, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with an increasing prevalence and has become a major public health problem in Lhokseumawe City. The successful management of T2DM is influenced by patients' characteristics and their level of adherence to treatment and self-care practices. This study aimed to identify the characteristics and adherence of patients with T2DM in Lhokseumawe City. A descriptive analytic study with a cross-sectional design was conducted in the working areas of community health centers (Puskesmas) in Lhokseumawe City in 2026. A total of 64 respondents were selected using purposive sampling. Data were collected using questionnaires on respondents' characteristics and adherence to T2DM management. The results showed that the respondents had a mean age of 69.95 years. Most respondents had completed senior high school education (53.1%), had a monthly income of less than IDR 2,700,000 (75.0%), and all respondents were Muslims and belonged to the Acehnese ethnic group. Regarding treatment adherence, the majority of respondents (81.3%) were categorized as adherent, while 18.8% were categorized as non-adherent. Adherence was influenced by several factors, including educational level, family support, cultural values, economic conditions, and patients' understanding of diabetes management. The study concludes that the socio-cultural characteristics of the community play an important role in influencing adherence among patients with T2DM. Therefore, culturally tailored health education and strengthened family support are recommended to improve diabetes management and optimize patient outcomes.